Pelatihan Peningkatan Mutu Sumber Daya Manusia Secara Kompetitif Di Era Global Pada PT. Rafaradis Jaya Abadi Pekanbaru - Adriansyah, Henry Martin (EL-EMIR INSTITUTE, 2026)
This community service activity aims to improve the quality of competitive human resources (HR) in facing the challenges of the global era at PT. Rafaradis Jaya Abadi Pekanbaru. Improving HR quality is considered a strategic factor in supporting company productivity and competitiveness. The implementation method of the community service activity consists of the stages of preparation, implementation, and evaluation. The training activities were carried out using lecture methods, interactive discussions, case studies, and work simulations, focusing on enhancing technical and non-technical competencies, work professionalism, and readiness to adapt to global changes. The results of the activity indicate an improvement in employees’ understanding, skills, and work attitudes, particularly in communication, teamwork, problem-solving, and awareness of the importance of continuous competency development. In addition, the training also encouraged better employee motivation and work ethic. The recommendation from this activity is the need for continuous HR training that is integrated with company policies to maintain and enhance human resource competitiveness optimally.